2020
DOI: 10.1007/s10549-020-05896-9
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer mortality and overdiagnosis after implementation of population-based screening in Denmark

Abstract: Introduction Service breast cancer screening is difficult to evaluate because there is no unscreened control group. Due to a natural experiment, where 20% of women were offered screening in two regions up to 17 years before other women, Denmark is in a unique position. We utilized this opportunity to assess outcome of service screening. Materials and methods Screening was offered in Copenhagen from 1991 and Funen from 1993 to women aged 50-69 years. We used difference-indifferences methodology with a study gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Hence the relationship between participation regularity and the risk of advanced stage breast cancer at diagnosis can be biased. To evaluate the effect of overdiagnosis on the association between screening regularity and the risk of advanced stage breast cancer at diagnosis in our estimation, a sensitive analysis assumes a 10% overdiagnosis rate derived from the Dutch population [22,23] was performed, since the level of overdiagnosis in Flanders breast cancer screening programme has not been reported in literature, we applied the data from the Dutch population which is geographically nearby the Flanders region [24][25][26][27][28][29][30][31]. In this sensitivity analysis, a random 10% of early stage screen-detected breast cancers were excluded and the modeling was done in the rest of the cases, since by definition, overdiagnosis is due to the detection of breast cancer that are not progressive at early stage by screening mammograms.…”
Section: Discussionmentioning
confidence: 99%
“…Hence the relationship between participation regularity and the risk of advanced stage breast cancer at diagnosis can be biased. To evaluate the effect of overdiagnosis on the association between screening regularity and the risk of advanced stage breast cancer at diagnosis in our estimation, a sensitive analysis assumes a 10% overdiagnosis rate derived from the Dutch population [22,23] was performed, since the level of overdiagnosis in Flanders breast cancer screening programme has not been reported in literature, we applied the data from the Dutch population which is geographically nearby the Flanders region [24][25][26][27][28][29][30][31]. In this sensitivity analysis, a random 10% of early stage screen-detected breast cancers were excluded and the modeling was done in the rest of the cases, since by definition, overdiagnosis is due to the detection of breast cancer that are not progressive at early stage by screening mammograms.…”
Section: Discussionmentioning
confidence: 99%
“…Another recent cohort study from Sweden of attendees and non‐attendees used a Markov model to estimate overdiagnosis and concluded it was minimal 14 . A cohort study from Denmark of invitation reported almost no overdiagnosis 11,15 …”
Section: Discussionmentioning
confidence: 99%
“…14 A cohort study from Denmark of invitation reported almost no overdiagnosis. 11,15 For an Australian case-control study included in the IARC handbook, 41 we calculated the odds ratio for all breast cancer in relation to ever having attended BreastScreen of 1.15 (CI 1.09-1.22), giving an attributable fraction of 13.4%. The study did not exclude women who previously had mammography or other breastrelated diagnostic procedures through Medicare.…”
Section: Overdiagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…The literature in this field is rich with various study designs (e.g., randomized clinical trials, case‐control studies, the difference‐in‐difference designs, etc. ; Adami et al., 2020; Lynge et al., 2020; Maroni et al., 2020), outcome measures (e.g., incidence, mortality, number needed to screen, stage shift, survival probability, etc. ; Duffy & Smith, 2020; Owens et al., 2022; Rembold, 1998), and comparisons used to evaluate CSPs.…”
Section: Introductionmentioning
confidence: 99%